(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Most commonly known by the famous three letters ’M.G.R.’, he was the most charismatic leader who founded the party AIADMK in 1972 and was catapulted to power. He became the Chief Minister of Tamilnadu in 1977 and remained in power till December 24, 1987. He made his film debut in 1936, and by the end of 1940, he had risen to the top of the acting ladder. MGR has been an admirer and supporter of Annadurai, the founder of the DMK Party, and has worked closely with him in all of his political endeavors. His charismatic appeal was crucial to the growth of the DMK party as well as his own political image. After untimely death of Annadurai in 1969, he was succeeded by M. Karunanidhi. He became the Chief Minister of Tamilnadu and the leader of the DMK party in 1969. Soon after, disagreements arose between him and the then Chief Minister M. Karunanidhi. Following his expulsion from the DMK, MGR formed a new party in the year 1972. The political climate in Tamilnadu had become so charged by a series of events that MGR was determined to run in the general election in 1977. His archrival, the DMK, was defeated in the election. He emerged as the state’s most successful leader and assumed the position of Chief Minister in Tamil Nadu. After a brief spell, his government was removed from power by the Union government for four months, but he still led the AIADMK party to victory in 1980 and 1984 elections. M.G.R., has been widely acknowledged as the most spectacular and charismatic figures not only in celluloid world of Tamilnadu at also its vibrant political scenario. this article discussed about various schemes,projectes,programs of mgr government and we try to find out the ratio of beneficiaries.